Species Boundaries and Parapatric Speciation in the Complex of Alpine Shrubs, Rosa sericea (Rosaceae), Based on Population Genetics and Ecological Tolerances - Gao, Yun-Dong; Gao, Xin-Fen; Harris, Aj (Frontiers in Plant Science, 2019)
Discerning species boundaries among closely related taxa is fundamental to studying evolution and biodiversity. However, species boundaries in plants can be difficult to delimit due to frequent introgression, which can occur across species and genera and may leave an evolutionary footprint similar to ongoing divergence and speciation. In this study, we sought to determine species boundaries within between thetwo closely related alpine shrubs, Rosa sericea and R. omeiensiscomplex of alpine shrubs, using population genetics, environmental data and ecological niche modeling (ENM), and morphological traits. We analyzed populations of Rosa sericea and R. omeiensissericea complex using genetic markers comprising a fragment of the single-copy nuclear gene, LEAFY, micro-satellites (EST-SSR), and plastid DNA sequences. The DNA sequence data suggested clusters of populations consistent with geography but not with previously proposed species boundaries based on morphology. Nevertheless, we found that the ecological niches of the previously proposed species only partially overlap. Thus, we suspect that these species are in the process of parapatric speciation; that is, differentiating along an ecological gradient, so that they exhibit differing morphology. Morphology has previously been the basis of recognizing the species R. sericea and R. omeiensis, which are the most widely distributed species within a broader R. sericea complex that includes which are most frequent in the complex, and several other narrow endemics. Here, we recognize R. sericea and R. omeiensis as independent species based on morphological and ecological data under the unified species concept, which emphasizes that these data types are of equal value to DNA for recognizing species boundaries and refining taxonomic treatments. While the DNA data did not delimit species within the R. sericea complex, we expect to develop and utilize new, robust DNA tools for understanding speciation within this group in future studies.